Human footprints from Italy: the state of the art - Avanzini, Marco; Citton, Paolo; Mietto, Paolo; Panarello, Adolfo; Raia, Pasquale; Romano, Marco; Salvador, Isabella (Journal of Mediterranean Earth Sciences, 2020)
The ichnological record of human traces from Italy is rich and quite diversified. In recent years, the development and dissemination of various methodologies and technological facilities has implemented the re-analysis of this record, enabling to reach different, sometimes deeper, interpretations favoured by the integration of external data, both geological and palaeontological. The oldest occurrence of the human ichnological record from Italy is represented by the Middle Pleistocene ‘Devil’s Trails’ ichnosite in the “Foresta” area (Roccamonfina volcano, southern Italy), depicting human trackmakers trampling a pyroclastic flow deposit while descending a slope about 349 ka. Most of the record is Holocene in age and is constituted by the Upper Palaeolithic Grotta della Bàsura site (Toirano, northern Italy, about 14 ky), the protohistoric sites of Afragola, Nola and Palma, the area of Pompei and the site of Aosta. The record is enriched by the ichnological evidences preserved in military structures of Trentino region (northern Italy) during the First World War. An updated report and discussion of these sites is here provided.